Refugee Regime in the Prolonged Transit: The Role of Non-State Actors in Indonesia’s Fragmented Governance - Hasan, Finahliyah; Nandyatama, Randy W.; Kurniadi, Bayu D.; Apsari Dewi, Ni Made Diah (Refuge, 2024)
This research scrutinizes the refugee regime in Indonesia, highlighting the role of non-state actors within a fragmented governance framework. Despite not signing the 1951 Refugee Convention, Indonesia functions as a notable transit point for refugees and asylum seekers. Through qualitative analysis, the findings suggest that the collaborative yet fragmented system presents both opportunities and challenges in addressing the intricate needs of refugees in Indonesia. This study contributes to a deeper understanding of how non-state actors influence practical policy and procedures in providing and advocating refugee rights in contexts where formal state mechanisms are constrained or absent.